Faktor-Faktor yang Memengaruhi Kapasitas dan Kemandirian Belajar Penyuluh melalui E-Learning - Rospina, Pepi; Sumardjo, Sumardjo; Fatchiya, Anna; Anwas, Oos (Jurnal Penyuluhan, 2022)
The independence of learning based on e-learning needs to be owned by extension workers in order to be able to increase their insight and knowledge through accessibility to learning resources from the internet, which is expected to increase their capacity as extension workers. The research objectives are to analyze the factors affecting capacity and independent learning of extension workers through e-learning and to build a strategy to increase the independent learning of extension workers through e-learning. The study was conducted in Cianjur and Bogor Districts, and in the learning area of ​​Universitas Terbuka 2019. Respondents are 96 extension workers who take studying at UT in 2019 through census techniques, and 160 extension workers in Bogor and Cianjur Districts who were assigned cluster random sampling. The results show that the dominant factors affecting the capacity and the independent learning of extension workers through e-learning are: the level of ICT utilization and environmental factors. Strategies to strengthen the independent learning of extension workers are: (1) utilizing extension institutions in increasing training and extension activities through the use of ICT, (2) maintaining the facilitation of supporting facilities for extension workers learning through e-learning, (3)Improving the reward system for outstanding extension workers, (4) Increasing the strengthening of the quality and service of the cyber extension website as a reference for extension workers in carrying out the independent learning process, and (5) Providing various communication spaces in a well-managed network.The independence of learning based on e-learning needs to be owned by extension workers in order to be able to increase their insight and knowledge through accessibility to learning resources from the internet, which is expected to increase their capacity as extension workers. The research objectives are to analyze the factors affecting capacity and independent learning of extension workers through e-learning and to build a strategy to increase the independent learning of extension workers through e-learning. The study was conducted in Cianjur and Bogor Districts, and in the learning area of ​​Universitas Terbuka 2019. Respondents are 96 extension workers who take studying at UT in 2019 through census techniques, and 160 extension workers in Bogor and Cianjur Districts who were assigned cluster random sampling. The results show that the dominant factors affecting the capacity and the independent learning of extension workers through e-learning are: the level of ICT utilization and environmental factors. Strategies to strengthen the independent learning of extension workers are: (1) utilizing extension institutions in increasing training and extension activities through the use of ICT, (2) maintaining the facilitation of supporting facilities for extension workers learning through e-learning, (3)Improving the reward system for outstanding extension workers, (4) Increasing the strengthening of the quality and service of the cyber extension website as a reference for extension workers in carrying out the independent learning process, and (5) Providing various communication spaces in a well-managed network.